Pengaruh Media Tanam yang Berbeda terhadap Produktivitas Tanaman Kelor (Moringa oleifera) - Novita, Maulina; Mahlil, Yusuf; Habiyah, Umul; Ramadani , Dedi (Journal of Engineering Science and Technology Management, 2023)
Moringa (Moringa oleifera Lam.) is a type of tropical plant that is easy to grow in Indonesia. This plant is classified as a shrub with a height of about 7-11 meters and thrives in the lowlands up to an altitude of 700 meters above sea level. Moringa plants have the potential to increase livestock production, especially used as feed for ruminants. Currently research on moringa is mostly focused on nutritional quality and health value obtained, while research on optimal cultivation of moringa is still very little. In this study, the production of moringa plants grown on soil media was carried out with the addition of manure with different doses and sources on the production of moringa plants. This study used a completely randomized design (CRD) with three treatments and five replications, P0 = 2 kg of soil without fertilizer, P1 = 1 kg of soil and 1 kg of cow manure. P2 = 1 kg of soil and 1 kg of goat manure. The application of organic fertilizer resulted in a significant decrease in the height growth of Moringa plants. On the diameter of the stem, organic fertilizer has a significant effect on increasing the size of the stem diameter. On leaf growth, the application of organic fertilizers did not significantly affect the growth of plant leaves. Types of organic fertilizers that give the best effect are goat feces on plant height, cow feces and goat feces give the best effect on plant stem diameter.